PUBLIC CONTROL IN THE ADMINISTRATION OF GOVERNMENT AND PUBLIC AFFAIRS (Journal of Universal Science Research, 2023)
Another important legal basis for public control and its implementation in the management of society and state affairs is the Law of the Republic of Uzbekistan "On Environmental Control". It is noteworthy that this article states that public control can be carried out in cooperation with the mass media, non-governmental non-profit organizations and other organizations, that state bodies must assist citizens' self-government bodies in the implementation of public control and take timely measures in accordance with legal documents regarding their appeals. related norms were also strengthened.